The struggle within: Self-regulation profiles and challenges among health sciences students - Andriani, Annisa; Rahman, Marlita Andhika; Hafizah, Nurul; Annisa, Verdiantika; Azzahra, Fadia (Proceedings Academic Universitas Jambi, 2025)
Background: Mental health concerns among young adults in Indonesia continue to rise, with university students particularly vulnerable due to increasing responsibilities, developmental transitions, and environmental demands. Self-regulation is recognized as a key contributor to student resilience, yet empirical evidence in this context remains limited. Objective: This study examined the self-regulation profile of students at the Faculty of Medicine and Health Sciences, Universitas Jambi, and identified the specific challenges they face in applying self-regulation strategies. Methods: Using a descriptive quantitative design, data were collected from 41 students selected through quota sampling. Instruments included the Self-Regulation Scale adapted by Tresnadiani and Taufik (2020) and 12 open-ended questions assessing goal setting, decision making, and perseverance. Quantitative data were analyzed descriptively to categorize levels of self-regulation, while qualitative responses were examined through thematic coding. Results: Most respondents (63.4%) displayed a moderate level of self-regulation. Students demonstrated awareness of effective strategies such as prioritization and adapting to sudden changes; however, they struggled to apply these consistently due to internal barriers including procrastination, reduced motivation, and ineffective time management. Although they understood appropriate approaches—such as setting specific goals and establishing priorities—their implementation remained inconsistent, with many students prioritizing personal comfort when facing academic challenges. Conclusion: FKIK students possess adequate foundational knowledge of self-regulation but show limited consistency in applying these skills in daily life. Targeted interventions are recommended to help students overcome internal barriers, thereby strengthening self-regulation, resilience, and academic adaptation.